2012
DOI: 10.1007/7854_2012_199
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Selected Alcohol Preferring Rats to Model Human Alcoholism

Abstract: Animal models have been successfully developed to mimic and study alcoholism. These models have the unique feature of allowing the researcher to control for the genetic characteristics of the animal, alcohol exposure and environment. Moreover, these animal models allow pharmacological, neurochemical and behavioural manipulations otherwise impossible. Unquestionably, one of the major contributions to the understanding of the neurobiological basis of alcoholism comes from data that have been obtained from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 120 publications
(144 reference statements)
1
30
0
Order By: Relevance
“…Particularly germane to the present topic, animal models have led to important findings on neural substrates mediating addiction to multiple substances of abuse (c.f., Bell and Rahman, 2016; De Biasi, 2015; Dwoskin, 2014; Ekhtiari and Paulus, 2016a, 2016b; Frascella et al, 2011; Heidbreder, 2008; Koob et al, 2014a; McArthur and Borsini, 2008c; Nader, 2016; Olmstead, 2011) and ethanol in particular (Bell et al, 2005, 2006b, 2012, 2013, 2014, 2016; Ciccocioppo, 2013; Crabbe et al, 2013; Knapp and Breese, 2012; Maldonado-Devincci et al, 2012; McBride and Li, 1998; McBride et al, 2014b; Ramsden, 2015; Ryabinin, 2012). As indicated above, advanced neuroimaging techniques including resting state functional connectivity are being used to develop endophenotypes for medications development targeting AUDs (e.g., Brown et al, 2015; Cui et al, 2015; Ernst et al, 2015; Fedota and Stein, 2015; Gowin et al, 2015; Gullo et al, 2011; Moeller et al, 2016; Muller-Oehring et al, 2015a, 2015b; Schuckit et al, 2016; Squeglia et al, 2014).…”
Section: Background From An Animal Model Perspectivementioning
confidence: 99%
“…Particularly germane to the present topic, animal models have led to important findings on neural substrates mediating addiction to multiple substances of abuse (c.f., Bell and Rahman, 2016; De Biasi, 2015; Dwoskin, 2014; Ekhtiari and Paulus, 2016a, 2016b; Frascella et al, 2011; Heidbreder, 2008; Koob et al, 2014a; McArthur and Borsini, 2008c; Nader, 2016; Olmstead, 2011) and ethanol in particular (Bell et al, 2005, 2006b, 2012, 2013, 2014, 2016; Ciccocioppo, 2013; Crabbe et al, 2013; Knapp and Breese, 2012; Maldonado-Devincci et al, 2012; McBride and Li, 1998; McBride et al, 2014b; Ramsden, 2015; Ryabinin, 2012). As indicated above, advanced neuroimaging techniques including resting state functional connectivity are being used to develop endophenotypes for medications development targeting AUDs (e.g., Brown et al, 2015; Cui et al, 2015; Ernst et al, 2015; Fedota and Stein, 2015; Gowin et al, 2015; Gullo et al, 2011; Moeller et al, 2016; Muller-Oehring et al, 2015a, 2015b; Schuckit et al, 2016; Squeglia et al, 2014).…”
Section: Background From An Animal Model Perspectivementioning
confidence: 99%
“…Genetically selected Marchigian Sardinian alcohol preferring (msP) rats have been proposed as a phenocopy of animals in a post-dependent state (Ciccocioppo 2013; Ciccocioppo et al 2006). They have an innate high preference for alcohol, show excessive alcohol drinking [6–8 g/kg body weight per day (Ciccocioppo et al 2006)], are highly sensitive to stress and stress-induced alcohol seeking (Ciccocioppo 2013; Ciccocioppo et al 2006), have depressive-like symptoms that recover following alcohol consumption (Ciccocioppo et al 1999) and demonstrate an anxious-like phenotype (Hansson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They have an innate high preference for alcohol, show excessive alcohol drinking [6–8 g/kg body weight per day (Ciccocioppo et al 2006)], are highly sensitive to stress and stress-induced alcohol seeking (Ciccocioppo 2013; Ciccocioppo et al 2006), have depressive-like symptoms that recover following alcohol consumption (Ciccocioppo et al 1999) and demonstrate an anxious-like phenotype (Hansson et al 2006). In previous studies, we demonstrated that msP rats have an innate hyperfunction of the CRF system that is associated with the occurrence of two single nucleotide polymorphisms (SNPs) in the promoter region (position −1836 and −2097) of the gene encoding the CRF1-R (Gehlert et al 2007; Hansson et al 2007; Hansson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having an innate high preference for alcohol and for drinking excessive amounts of alcohol [6–8 g/kg body weight per day (Ciccocioppo et al 2006)], msP rats are highly sensitive to stress and stress-induced alcohol seeking (Ciccocioppo 2013; Ciccocioppo et al 2006), show depressive-like traits (Ciccocioppo et al 1999; Gozzi et al 2013) and demonstrate an anxious-like phenotype that recovers following alcohol drinking (Ayanwuyi et al 2013; Cippitelli et al 2015; Hansson et al 2006). In fact, msP rats have been proposed to phenocopy animals in a post-dependent state (Ciccocioppo 2013; Ciccocioppo et al 2006) that largely drink alcohol to self-medicate from negative affect and excessive anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, msP rats have been proposed to phenocopy animals in a post-dependent state (Ciccocioppo 2013; Ciccocioppo et al 2006) that largely drink alcohol to self-medicate from negative affect and excessive anxiety.…”
Section: Discussionmentioning
confidence: 99%